An Essay on Religious Value Evolution in Pars Special Economic Energy Zone, Iran - Abdolrasoul Fadaee Dowlat; Taghi Azadarmaki; Ali Baqaii Sarabi (توسعه اجتماعی, 2023)
Oil and gas industry development has been one of the most consequential drivers of social and cultural changes in the south of Iran in recent decades. Industrialization led to different kinds of socialization and brought new values to traditional societies. Religious values are one of the most important cultural values that societies have strong resistance to change. This research aims to shed light on industrial socialization's impact on religious values in Pars Special Economic Energy Zone (PSEEZ). Rapid industrial growth in PSEEZ led to pervasive intergenerational cultural changes that reshaped the religious values of these generations, bringing a shift from religious to secular views. We gathered data from a survey between residents (aged 18-65 years old). We divide the sample into three groups (who socialize before; during and after oil and gas industries development in this region). We use SPSS to compare religious values means between groups (ANOVA). The results show that religious values are less common across those below 25 years old. This group was born and socialized after industrial development in the field. The differences between the experiences of the post-industrial birth cohorts and all older cohorts produced significant differences in their religious value priorities and, respondents who grow in the industrial space have more secular beliefs. Simultaneous with value changes between generations that confirm the socialization hypothesis of Inglehart; some changes in older generations' values and some resistances of younger people's religious beliefs both emphasize on modification of Inglehart's socialization theory.